Prevalence and Characteristics of Intracranial and Extracranial Hemorrhages in Neonates with Hypoxic Ischemic Encephalopathy (HIE). (1st June 2016) - Vayalthrikkovil, S; Bashir, R A; Espinoza, L; Irvine, L; Mohammad, K
Abstract: BACKGROUND: Intracranial hemorrhages (ICH) and extracranial hemorrhages(ECH) are not uncommon in neonates with HIE. The risk factors of hemorrhages and their association with HIE severity and other therapeutic interventions are unclear. OBJECTIVES: To examine the prevalence and risk factors associated with ICH and ECH in neonates with HIE. DESIGN/METHODS: A retrospective cohort study of neonates admitted with HIE from September 2011 to October 2015 in a level III NICU. ICH[mainly subdural(SDH), intraventricular (IVH), intraparenchymal (IPH)] and ECH [mainly subgaleal(SGH) and cephalhematoma] were diagnosed by MRI.Perinatal and neonatal characteristics were examined, including mode of delivery, outborn status, HIE staging(using modified Sarnat scoring), therapeutic hypothermia(TH), clinical/EEG seizures, hypo/hypercarbia, inotrope use, thrombocytopenia-mild, moderate, severe(platelet count 100-150, 50-100, 1.8, activated partial thromboplas-tin time(aPTT)>45 sec, fibrinogen RESULTS: Number of HIE patients, n=157; median gestation 40 weeks(IQR 38-40); outborn=104(66%);TH used=103(66%);MRI brain done=138. . Prevalence of SDH, IPH, IVH and SGH were 47, 22, 9, 9 (34%, 16%, 6.5%, 6.5%) respectively. There was no significant increase in hemorrhage with mode of delivery except instrumentation, seizures, hypo/ hypercarbia, severe thrombocytopenia or deranged coagulation. Instrumental delivery significantly increased the prevalence of IPH and SGH. All hemorrhages except cephalhematoma increased with severity of HIE staging, but not with MRI severity. In the logistic regression analysis, use of dopamine was associated with increased risk of IPH(OR 2.94; 95% CI 1.42, 12.08) and trended towards increased risk of IVH (OR 4.49; 95% CI 0.98, 20.6). CONCLUSION: SDH followed by IPH are the common ICH. Despite being frequent, thrombocytopenia and deranged coagulation did not increase the risk of ICH or ECH in HIE; dopamine use associated with significant increase in the risk of IPH.